Assessing the sustained impact of a school-based obesity prevention program for adolescent boys: the ATLAS cluster randomized controlled trial. Issue 1 (December 2016) - Lubans, David; Smith, Jordan; Plotnikoff, Ronald; Dally, Kerry; Okely, Anthony; Salmon, Jo; Morgan, Philip
Abstract Background Obesity prevention interventions targeting 'at-risk' adolescents are urgently needed. The aim of this study is to evaluate the sustained impact of the 'Active Teen Leaders Avoiding Screen-time' (ATLAS) obesity prevention program. Methods Cluster RCT in 14 secondary schools in low-income communities of New South Wales, Australia. Participants were 361 adolescent boys (aged 12–14 years) 'at risk' of obesity. The intervention was based on Self-Determination Theory and Social Cognitive Theory and involved: professional development, fitness equipment for schools, teacher-delivered physical activity sessions, lunch-time activity sessions, researcher-led seminars, a smartphone application, and parental strategies. Assessments for the primary (body mass index [BMI], waist circumference) and secondary outcomes were conducted at baseline, 8- (post-intervention) and 18-months (follow-up). Analyses followed the intention-to-treat principle using linear mixed models. Results After 18-months, there were no intervention effects for BMI or waist circumference. Sustained effects were found for screen-time, resistance training skill competency, and motivational regulations for school sport. Conclusions There were no clinically meaningful intervention effects for the adiposity outcomes. However, the intervention resulted in sustained effects for secondary outcomes. Interventions that more intensively target the home environment, as well as other socio-ecological determinants of obesity may be needed to prevent unhealthy weight gain in adolescents from low-income communities. Trial registration Australian Clinical Trial RegistryACTRN12612000978864 .